An Investigation into EFL Students’ Experiences toward the Use Of Moodle and Its Implementation Challanges at Institut Parahikma Indonesia - RAHMAN, PATUR (ETERNAL (English, Teaching, Learning, and Research Journal), 2023)
An Investigation into EFL Students’ Experiences toward The Use Of MoodleTM and Its Implementation Challenges at Institut Parahikma Indonesia. The objectives of the research were to investigate the EFL Students’ experiences toward the use of MoodleTM features and to find out the challenges of Its implementation in Institut Parahikma Indonesia. The researcher applied the descriptive case study as the design in this research. Data obtained by the particular phenomenon is concerned with the experiences from the perspectives individually from interviews. There were 7 respondents consisting of 4 EFL students, 2 lecturers, and a high policy maker in Institut Parahikma Indonesia. They were chosen by their capability in understanding and utilizing MoodleTM. The results showed that the MoodleTM features in Institut Parahikma were up to date. However, the usage of It was only focused on task submission while there were many other features that were unused by the respondents. Furthermore, besides network issues still becoming an obstacle, lack of feedback in task submission made the students unable to evaluate their own abilities in learning. In addition, the result showed the challenges for Institut Parahikma in the future such as appreciation, technological literacy, and lack of Affective control for students. Keywords: MoodleTM, Students’ Experiences, Technological Literacy, Challenges.